Algorithms for the management of frontal sinus fractures: A retrospective study. Issue 10 (October 2022) - Calis, Mert; Kaplan, Güven Ozan; Küçük, Kutluhan Yusuf; Altunbulak, Ahmet Yasir; Akgöz Karaosmanoğlu, Ayça; Işıkay, Ahmet İlkay; Mavili, Mehmet Emin; Tunçbilek, Gökhan
Abstract: The aim of this study was to evaluate the long-term results and to evaluate the validity of the treatment algorithm that can be safely applied in dfrontal sinus fractures. All patients were evaluated in terms of late-term contour deformity and further craniometric analysis for measurement of maximum amount of displacement, fracture surface area (mm 2 ) and the maximum angulation of the fracture (degree) were done. 125 patients (101 male, 24 female) with frontal sinus fractures with an average age of 22.4 years (range, 17–66 years) were reviewed. All patients with isolated anterior table fractures without displacement were followed up on conservative basis. 33 patients with anterior table fractures with displacement and 39 patients with anterior and posterior table fractures were also followed on conservative basis without surgical intervention. The cut-off value of the maximum amount of displacement was confirmed to be 4.5 mm in prediction of late-term contour deformities (p < 0.001). The maximum amount of displacement was decreased by an average of 1.8 mm at late-term. Apart from the standard protocols, within the limitations of the study it seems that isolated anterior table fractures with a maximum amount of displacement of less than 4.5 mm can be treated conservatively without leading to contour deformities. CSF leakage in the acute setting might not always require cranialization and this may spontaneously resolve within 10 days. Cranialization should be considered whenever CSF leakage lasts longer than 10 days.